Does Internship Experience Beget Academic Relevance and Employment Prospects: An Assessment of Graduate Interns from a Nigerian University - A. B. Adebakin (University of Sofia, 2015)
Basically, the objective of internship programme is to expose students to the real world of work and in the process, provide feedback to institutions on the relevance or otherwise of the curriculum. This study therefore assessed the academic relevance of internship programme and employment prospect of graduate interns from Obafemi Awolowo University, Ile-Ife, Nigeria. Population of the descriptive study were graduate students in the Department of Educational Management of the university. A sample of 120 graduate students from 2012/2013, 2013/2014 and 2014/2015 academic sessions were randomly selected. The post internship semester results, a structured interview and a Likert scale type questionnaire were used in the study. The Cronbach alpha reliability test on the questionnaire showed 0.79 reliability index. Descriptive and inferential statistics were used at 5% level of significance. The study found that graduate students participation in internship has impact on academic performance and also has a significance influence on employment prospect. It was recommended that internship should be geared towards enhancing the knowledge, skills, attitude and personality of graduate students to prepare them in more holistic approach for employment.